ASUPAN GULA, GARAM, DAN LEMAK DI INDONESIA: Analisis Survei Konsumsi Makanan Individu (SKMI) 2014 - Atmarita, Atmarita; Jahari, Abas B; Sudikno, Sudikno; Soekatri, Moesijanti (GIZI INDONESIA, 2016)
ABSTRACTIndonesia is facing a very complex health problems. Non-communicable diseases is increasing, while infectious diseases still quite dominant. Among other contributing factors is the imbalance of daily required nutrients intake. Overweight is closely associated with daily intake level of consumed foods, especially the calorie contributors such as sugar and fat, besides, excessive salt intake drives people to eat more. This article is intended to determine the intake of sugar, salt and fat of Indonesian population that is exceeding the WHO recommendations. The analysis used the data of Individual Food Consumption Survey or SKMI 2014 that collected data and asked all food consumed in the last 24 hours from 45,802 households and 145,360 household members in all provinces in Indonesia. Descriptive analysis of all 17 food groups was undertaken to calculate the intake level of sugar, salt, and fat of each individual, and also calculated the proportion based on the characteristics of age group, sex, place of residence, socio-economic, and by province as well. The analysis showed that 77 million people or 29.7 percent of Indonesia's population consumed sugar, salt, and fat exceeding WHO recommendations: sugar (> 50 g/day), salt (> 5 g/day), and fat (> 67 g/day). This should be anticipated due to the increasing trend of people with non-communicable diseases, such as obesity, hypertension, diabetes mellitus, and stroke which have already apparent from 2007 to 2013. It was suggested to reduce the intake of sugar, salt, and fat need of the population through advocacy, counseling, socialization at schools, food and beverage industries, restaurants, factories, and other relevant institutions.ABSTRAKIndonesia menghadapi masalah kesehatan yang sangat kompleks. Penyakit tidak menular semakin meningkat, sementara penyakit menular masih cukup dominan. Faktor penyebabnya antara lain adalah tidak seimbangnya asupan zat gizi yang dibutuhkan sehari-hari. Kelebihan berat badan sangat erat kaitannya dengan konsumsi makanan sehari-hari, terutama penyumbang kalori, seperti gula dan lemak, selain asupan garam yang cenderung membuat orang untuk mengonsumsi makan lebih banyak. Artikel ini ditujukan untuk mengetahui asupan gula, garam, dan lemak penduduk Indonesia yang melebihi rekomendasi WHO. Analisis menggunakan data Survei Konsumsi Makanan Individu (SKMI) 2014 yang mengumpulkan data dan menanyakan semua yang dikonsumsi 24 jam terakhir dari 45.802 rumah tangga dan 145.360 anggota rumah tangga di seluruh provinsi di Indonesia. Analisis deskriptif dari ke-17 kelompok makanan dilakukan untuk menghitung asupan gula, garam, dan lemak (GGL) dari setiap individu, dan juga dihitung proporsi berdasarkan karakteristik: kelompok umur, jenis kelamin, tempat tinggal, sosial-ekonomi, dan juga menurut provinsi. Hasil analisis menunjukkan bahwa 29,7 persen penduduk Indonesia atau setara dengan 77 juta jiwa sudah mengonsumsi GGL melebihi rekomendasi WHO: gula (>50 gram/hari), garam (>5 gram/hari), dan lemak (>67 gram/hari). Hal ini perlu diantisipasi mengingat kecenderungan meningkatnya penderita penyakit tidak menular, seperti: obesitas, hipertensi, diabet mellitus, dan stroke yang sudah jelas dari tahun 2007 ke tahun 2013. Saran untuk mengurangi asupan GGL ini perlu segera dilakukan dengan target seluruh penduduk, melalui advokasi/penyuluhan/sosialisasi di sekolah, industri makanan-minuman, restoran, pabrik, dan institusi terkait lainnya. Kata kunci: asupan gula-garam-lemak, penyakit tidak menular, penduduk Indonesia